Eiger Coffee Marketing Strategy in Makassar - Nurul Aulia Achmad; Hasnawi Haris; Muh Rizal (Universitas Negeri Makassar, 2021)
This research aims to find out the marketing strategy of Eiger Coffee Makassar, where the data analysis techniques used are SWOT analysis techniques (Strength, Weakness, Opportunities, Threats). Researchers also find out what Eiger coffee Makassar's marketing strategy looks like by using marketing strategy formulation, namely segmentation strategy, target market strategy, and market positioning strategy. Besides, researchers also found out the marketing mix of Eiger Coffee Makassar. This research uses a qualitative approach with descriptive analysis research type. The informants in this study are Manager / Leader Barista Eiger Coffee Makassar, Employees Eiger Cofee Makassar, and Consumer Eiger Coffee Makassar. Data collection techniques through observation methods, interviews, and documentation. The data obtained from the research results are processed using data reduction analysis, data presentation, and conclusion drawing. The results of this study showed that Eiger Coffee Makassar Marketing Strategy on the formulation of Eiger coffee segmentation marketing strategy is focused on consumers who are looking for coffee with good quality and taste but have relatively cheaper prices, targeting Eiger Coffee is a coffee lover consumer who is looking for quality and taste there is no certain age limit, and positioning Eiger Coffee into a coffee shop that focuses on the quality of products served at affordable prices. The marketing mix at Eiger Coffee Makassar includes the product, price, place, and promotion run quite well. While the results shown by swot matrix analysis where the cartesian diagram is in the first quadrant shows that the most appropriate strategy for Eiger Coffee Makassar is SO Strategywhich utilizes Strength to maximize Opportunities.